Innovation in the use of mung bean flour and wheat flour with the addition of Pak choy puree to chicken gyoza skin as a high-protein food - Abdi, Yenny Febriana Ramadhan; Maynar, Angel Lestari; Rochmah, Alfi Nur; Suleman, Dininurilmi Putri; Nadhilah, Dini (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
The utilization of mung bean flour as a nutritional enhancer in food processing can serve as a preference for increasing protein content. One type of food product that can incorporate mung bean flour is gyoza. Gyoza wrappers are typically made from wheat flour with low protein content. Mung bean flour can be added to improve its protein content. Additionally, mung bean flour in gyoza wrappers can be combined with fresh antioxidant-rich ingredients, such as Pak choy, to enhance antioxidant activity. This study aimed to determine the effect of using mung bean flour and wheat flour with the addition of Pak choy puree on chicken gyoza's sensory and chemical quality. The research employs a Completely Randomized Design (CRD) with a non-factorial approach, using four formulations: F0 (150 g wheat flour), F1 (100 g wheat flour and 50 g mung bean flour), F2 (75 g wheat flour and 75 g mung bean flour), and F3 (50 g wheat flour and 100 g mung bean flour). The obtained data were analyzed using ANOVA (analysis of variance) followed by the DMRT test at a 5% significance level. The results from the sensory evaluation indicate that the best formulation was the chicken gyoza sample with 50 g of mung bean flour and 100 g of wheat flour. The chemical analysis results for this formulation include moisture content (53.3%), protein content (11.23%), fat content (2.63%), and antioxidant activity (4.83%).